2010
DOI: 10.1002/ajim.20899
|View full text |Cite
|
Sign up to set email alerts
|

Occupational demands and health effects for bricklayers and construction supervisors: A systematic review

Abstract: for bricklayers evidence was found for physical demands and risk on low back pain and complaints of arms and legs, for construction supervisors on psychosocial demands. Both occupations are at increased risk of lung cancer and injuries. Job-specific demands and health effects should be incorporated in WHS for construction workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 80 publications
(167 reference statements)
2
67
0
Order By: Relevance
“…The risk factors for MSD among bricklayers have been well documented from several workplace studies (step 2), with manual materials handling being the most prominent (87,88). These studies showed that for bricklaying assistants, manual materials handling needed for transportation of bricks, blocks and mortar is the most physically demanding task.…”
Section: Example 2: Msd and Bricklaying Workmentioning
confidence: 95%
See 1 more Smart Citation
“…The risk factors for MSD among bricklayers have been well documented from several workplace studies (step 2), with manual materials handling being the most prominent (87,88). These studies showed that for bricklaying assistants, manual materials handling needed for transportation of bricks, blocks and mortar is the most physically demanding task.…”
Section: Example 2: Msd and Bricklaying Workmentioning
confidence: 95%
“…A recent review showed that bricklayers have an increased risk of developing MSD, including LBP and pain in the upper and lower extremities (87), with bricklayers experiencing even more MSD than other construction workers (88) (step 1). The risk factors for MSD among bricklayers have been well documented from several workplace studies (step 2), with manual materials handling being the most prominent (87,88).…”
Section: Example 2: Msd and Bricklaying Workmentioning
confidence: 99%
“…Construction work is among the jobs most commonly associated with high physical load and the prevalence of musculoskeletal disorders (MSD), especially low back pain and neck/shoulder pain (Boschman et al 2012). Furthermore, construction work is characterised by a high degree of heavy lifting and working positions with forward and side bending of the trunk (Boschman et al 2011) which have shown to increase the risk of MSD (Mayer, Kraus, and Ochsmann 2012). As a result, a study by Alavinia, van Duivenbooden, and Burdorf (2007) suggests that interventions should focus on reducing the physical workload for construction workers as a high physical load is related to a gradual loss of working ability (Alavinia, van Duivenbooden, and Burdorf 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Masonry activities such as mixing mortar, installing scaffold, cutting and laying block are labour intensive and need diverse skills in the masons to execute their tasks. Masonry is physically demanding (Spielholz et al, 2006) as masons and helpers have to stand for long episodes of time and lift heavy material (Boschman et al, 2011). Masons' work is substantially based on outdoor operations which expose masons to poor weather conditions which in turn reduces their productivity.…”
Section: Introductionmentioning
confidence: 99%